Beyond the Capture of Circulating Tumor Cells: Next‐Generation Devices and Materials. Issue 4 (8th December 2015) - Green, Brenda J.; Saberi Safaei, Tina; Mepham, Adam; Labib, Mahmoud; Mohamadi, Reza M.; Kelley, Shana O.
Abstract: Over the last decade, significant progress has been made towards the development of approaches that enable the capture of rare circulating tumor cells (CTCs) from the blood of cancer patients, a critical capability for noninvasive tumor profiling. These advances have leveraged new insights in materials chemistry and microfluidics and allowed the capture and enumeration of CTCs with unprecedented sensitivity. However, it has become increasingly clear that simply capturing and counting tumor cells launched into the bloodstream may not provide the information needed to advance our understanding of the biology of these rare cells, or to allow us to better exploit them in medicine. A variety of advances have now emerged demonstrating that more information can be extracted from CTCs with next‐generation devices and materials featuring tailored physical and chemical properties. In this Minireview, the last ten years of work in this area will be discussed, with an emphasis on the groundbreaking work of the last five years, during which the focus has moved beyond the simple capture of CTCs and gravitated towards approaches that enable in‐depth analysis. Abstract : Deadliest catch : Over the last decade, significant progress has been made towards the capture of rare circulating tumor cells (CTCs) from the blood of cancer patients, a critical capability for noninvasive tumor profiling. This Minireview summarizes recent breakthroughs and focuses on how new devices and materials have allowed this rapidly advancing field to move beyond enumeration and towards comprehensive characterization of CTCs.